Three‐spined stickleback armour predicted by body size, minimum winter temperature and pH. (20th February 2020) - Smith, C.; Zięba, G.; Spence, R.; Klepaker, T.; Przybylski, M.
Abstract: Similar phenotypes evolve under equivalent environmental conditions through parallel evolution. Because they have repeatedly invaded and adapted to new freshwater environments, the three‐spined stickleback ( Gasterosteus aculeatus ) offers a powerful system for understanding the agents of selection in nature that drive parallel evolution. Here, we examine the ecological and environmental variables responsible for morphological variation in three‐spined stickleback populations across its European range. We collected fish from 85 populations, encompassing much of the European latitudinal range of the species and including lowland rivers and lakes, coastal lagoons and moorland ponds. We measured biotic and environmental variables at all sites along with morphological traits for 2, 358 individuals. Using an information theory approach, we identified body size, minimum average winter temperature and pH as primary predictors of stickleback armour evolution, challenging current hypotheses for stickleback morphological diversification and demonstrating the fundamental role played by body size and scaling in mediating responses to selection. Stickleback lateral plate phenotype represents a potentially powerful tool for monitoring change in climate variables across the northern temperate region. Abstract : We address the question of what environmental variables select for armour reduction in freshwater populations of the three‐spined stickleback, a model species in evolutionary ecology. We show, contrary to current hypotheses, that body size and variables influencing body size are the strongest predictors of variation in armour evolution. These findings imply a key role for scaling in armour evolution.